Access to mental health services: The experiences of people with intellectual disabilities. Issue 2 (10th October 2018) - Whittle, Erin Louise; Fisher, Karen Raewyn; Reppermund, Simone; Trollor, Julian
Abstract: Background: People with intellectual disability experience higher rates of mental health disorders than the rest of the population, and expert opinion holds that multiple barriers prevent people with intellectual disability from accessing appropriate services. Methods: A qualitative study was designed to explore the lived experience of barriers and enablers to access to mental health services among people with intellectual disability. Interviews and focus groups were conducted with people with intellectual disability, carers and service providers. Results: Barriers and enablers were identified across four key dimensions of access: utilization of services; service availability; relevance, effectiveness and access; and equity and access. These factors operated at both systemic and personal levels. Conclusions: The findings from this study provide empirical evidence of anecdotal experiences of access to mental health services and provide insight into the ways users, carers and service providers navigate an often hostile system and indicate further directions for research.